Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/id.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide Therapy for Bisphosphonate-Related Osteonecrosis of the Jaw Associated With Dental Implants

Abstract: This report describes a case of teriparatide (TPTD) therapy for bisphosphonate (BP)-related osteonecrosis of the jaw induced after implant placement. A 75-year-old woman taking oral BP was referred with uncontrolled osteonecrosis of the mandible related to the implant placement. With conservative treatment, BP was suspended and daily subcutaneous injections of 20 μm/d TPTD were started. After 4 months of the therapy, fixture removal and sequestrectomy were performed. Histological analysis revealed necrotic lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Accordingly, these clinical and experimental data might be related to the successful use of human recombinant parathyroid hormone (rhPTH), a bone anabolic strategy, as a therapeutic approach for BONJ in the clinic. (Doh et al 2015;Khan et al 2015). (Santini et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these clinical and experimental data might be related to the successful use of human recombinant parathyroid hormone (rhPTH), a bone anabolic strategy, as a therapeutic approach for BONJ in the clinic. (Doh et al 2015;Khan et al 2015). (Santini et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(Doh et al, 2015;Kakehashi et al, 2015;Neuprez, Rompen, Crielaard, & Reginster, 2014). (Doh et al, 2015;Kakehashi et al, 2015;Neuprez, Rompen, Crielaard, & Reginster, 2014).…”
Section: Medical Management Of Onjmentioning
confidence: 99%
“…Therapeutic strategies for ONJ include a wide range of therapeutic options, from conservative treatments to surgical procedures. (Doh et al, 2015;Kakehashi et al, 2015;Neuprez, Rompen, Crielaard, & Reginster, 2014). Teriparatide treatment can produce favourable results even in previously refractory ONJ .…”
Section: Medical Management Of Onjmentioning
confidence: 99%
“…Many previous studies have shown that the intermittent administration of PTH (1-34) increases the systemic bone mass, strength, and BMD (Hock, Gera, Fonseca, & Raisz, 1988;Shen et al, 1998), prevents bone loss (Liu & Kalu, 1990), facilitates the healing of bone fractures (Aspenberg et al, 2010), and also reverses the reductions in the number and activity of osteoblasts induced by radiotherapy (Chandra et al, 2014). In dentistry, the intermittent administration of PTH inhibits periodontitis by preventing alveolar bone loss (Marques et al, 2005;Miller, Hunziker, Mecham, & Wronski, 1997), enhances osseous wound healing (Bashutski et al, 2010), and prevents and treats medication-related osteonecrosis of the jaw (Doh et al, 2015;Kim et al, 2014;Kuroshima, Entezami, McCauley, & Yamashita, 2014). The intermittent administration of PTH (1-34) also enhances bone formation of the implants and bone graft materials used in both orthopedics and dentistry (Almagro et al, 2013;Ohkawa, Tokunaga, & Endo, 2008).…”
Section: Introductionmentioning
confidence: 99%